The wood charcoal evidence from renewed excavations at Elands Bay Cave, South Africa - (:unkn) unknown (My University, 2016)
This article presents the results of the anatomical identification by scanning electron microscopy of wood charcoal from excavations in 2011 at Elands Bay Cave (EBC), South Africa. The samples are from Robberg Group D layers (18/19 ka cal BP); the Early Later Stone Age (LSA) Group F layers (22-24 ka cal BP), and the late Middle Stone Age (MSA) Group H-I-J layers (35-39ka cal BP). Noticeable differences in the vegetation are present in LSA layers, which have more diverse thicket elements represented in Groups D and F than in Group H-I-J layers-with their heavier reliance on Afromontane and mesic thicket taxa during the late MSA. Published charcoal results from previous excavations at EBC chart a progressive change over time from xeric thicket and asteraceous shrubland vegetation, through proteoid fynbos and general thicket to mesic thicket, riverine woodland and proteoid fynbos, ultimately to Afromontane forest. Climatic or soil moisture factors may have played a significant part and contributed to some or all of the taxa having very different phytogeographical distributions compared to their modern counterparts, but is also necessary to consider to what extent the people using EBC at different times might have collected (and selected) woody resources from a mosaic of vegetational communities, some local, some far away.
Keywords: African Research